Mammoplasty: steps for safe surgery. Evidence from literature - Paulo Rogério Quieregatto do Espirito Santo; Daniela Francescato Veiga; Ricardo Frota Boggio; Felipe Lehmann Coutinho; Anne Groth; Adriano Guimarães Brasolin; Lydia Masako Ferreira (Revista Brasileira de Cirurgia Plástica)
Introduction: Mammoplasty is one of the most performed surgeries by plastic surgeons. Like every procedure, it is not free of risks or complications. Objectives: Discuss controversial issues and complications in breast surgery and main treatments. Methods: Four full members of the SBCP with extensive experience in breast plastic surgery participated in the discussion, in addition to the regent of the mammoplasty chapter. Factors that presented the greatest controversy in mammoplasties were evaluated: use of antibiotics; preoperative infiltration; association of mammoplasty with breast implants; large mammary ptoses; masculinizing mammoplasty; flaps for the elevation of the nippleareola complex (NAC); use of drains; dressings in mammoplasties and fat grafting. Results: The literature and discussion among specialists generated the observations: there is robust evidence of the effectiveness in the use of perioperative antibiotics of reducing mammoplasties, but there is no evidence of benefits in maintaining use for more than 24 hours; preoperative infiltration with vasoconstrictor solutions does not reduce the incidence of hematoma; in mammoplasty associated with implants there was no consensus on the best technique, plane or texture of the implant; there was no consensus on the best technique in the elevation of NAC in large ptoses, whether grafts or flaps; masculinizing mammoplasty does not present complications different from those found in the literature; there is no specific protocol for conduct when there is suffering from the NAC; dressings can be removed on the first postoperative day or kept longer, and there should be parsimony in the fat graft. Conclusion: The present study concluded that mammoplasty is safe surgery, but continued studies are needed to minimize complications.